Challenges and opportunities for integration in health systems: An Australian perspective - Petrich, Mark; Ramamurthy, Vijaya; Hendrie, Delia; Robinson, Suzanne (Pavillion Publishing, 2013)
Purpose: The purpose of this paper is to contribute an Australian perspective to the debate on health system integration by identifying some key Australian challenges to integration, policy responses to enhance integration and potential insights from these for international policy makers, researchers and practitioners. Design/methodology/approach: Drawing on the systems theory concept of entropy, the authors contend that there exist factors that contribute to system fragmentation. Whilst policy responses to these challenges are contextual, there are generalisable features worth exploring internationally. Findings: The authors suggest that recognition of inherent system-based barriers is an important initial stage in moving towards integration. Whilst process and people factors are important contributors to integration, the political will to move in this direction is a necessary dynamic to energise the system through appropriate funding, incentives and governance structures. Originality/value: The paper provides a fresh Australian perspective to the international discourse on barriers and opportunities to enhance health system integration.